Job satisfaction and the labor market institutions in urban China - John S. Heywood; William Stanley Siebert; Xiangdong Wei (Institute for the Study of Labor (IZA), 2009)
The determinants of worker job satisfaction are estimated using a representative survey of three major cities in China. Legally segregated migrants, floaters, earn significantly less than otherwise equivalent non-migrants but routinely report greater job satisfaction, a finding not previously reported. We confirm a positive role for membership in the communist party but find that it exists only for non-migrants suggesting a club good aspect to membership. In contrast to earlier studies, many controls mirror those found in western democracies including the paradox of the contented female worker.
urn:nbn:de:101:1-20090703165
Keywords: J28; J61; O17; D73; 330; Arbeitszufriedenheit; Binnenwanderung; Städtischer Arbeitsmarkt; Kommunistische Partei; Mitgliedschaft; China